Odpowiedzi

2009-10-08T19:38:37+02:00
-2*(-7)+44:(-11)-78:(39)= 14+ (-4) + 2= 12

-40:[-4*(-3)-5*(7-3)]= -40:[12-20]= -40: (-8)= 5

[10*(-2)-7*3]*(-4)= [-20-21] * (-4) = -41 * (-4)= 164

[-15*(-5)+10*(-3)]:9= (75-30) : 9= 45 : 9= 5
2009-10-08T19:41:27+02:00
-2*(-7)+44:(-11)-78:(39)=14+44:(-11)[-78:39=-2]= 58:_-13)=4,46
-40:[-4*(-3)-5*(7-3)]=-40:[12-20]=-40:(-8)=5
[10*(-2)-7*3]*(-4)=(-20-21)*-4=164
[-15*(-5)+10*(-3)]:9=75+(-30):9=5
2009-10-08T20:45:56+02:00
-2*(-7)+44:(-11)-78:(39)= 14+(-4)-(-2)=8
-40:[-4*(-3)-5*(7-3)]=-40:[12-20]=40:(-8)=-5
[10*(-2)-7*3]*(-4)=[-20-21]*(-4)=-41*(-4)=164
[-15*(-5)+10*(-3)]:9=[75+(-30)]:9=45:9=5